2011
DOI: 10.1111/j.1460-9568.2010.07558.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and morphological consequences of human α-synuclein expression in a mouse α-synuclein null background

Abstract: A consensus about the functions of human wild-type or mutated α-synuclein (αSYN) is lacking. Both forms of αSYN are implicated in Parkinson’s disease, whereas the wild-type form is implicated in substance abuse. Interactions with other cellular proteins and organelles may meditate its functions. We developed a series of congenic mouse lines containing various allele doses or combinations of the human wild type αSYN (hwαSYN) or a doubly mutated (A30P*A53T) αSYN (hm2αSYN) in a C57Bl/6J line spontaneously deleted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 85 publications
0
10
0
Order By: Relevance
“…Although no significant differences between control and α -syn KO mice were found for evoked calcium activity and evoked spiking activity, α -syn KO mice exhibited a nonsignificant trend toward increases in the frequency and amplitude of spontaneous activity and in the fraction of imaged neurons exhibiting calcium alterations. Previous studies in α -syn KO mice reported only a mild synaptic deficit with subtle alterations in dopaminergic transmitter release (Abeliovich et al, 2000; Prasad et al, 2011). However, α -syn plays a role in the normal synaptic assembly.…”
Section: Discussionmentioning
confidence: 94%
“…Although no significant differences between control and α -syn KO mice were found for evoked calcium activity and evoked spiking activity, α -syn KO mice exhibited a nonsignificant trend toward increases in the frequency and amplitude of spontaneous activity and in the fraction of imaged neurons exhibiting calcium alterations. Previous studies in α -syn KO mice reported only a mild synaptic deficit with subtle alterations in dopaminergic transmitter release (Abeliovich et al, 2000; Prasad et al, 2011). However, α -syn plays a role in the normal synaptic assembly.…”
Section: Discussionmentioning
confidence: 94%
“…However, in a model with double mutant (A30P/A53T), apparent neurites dystrophy was reported. This phenotype was accompanied by deterioration in motor activity and neuronal aggregates [61]. These models are useful to elucidate the function of α-Synuclein related neurodegeneration, though the clinical relevance of this model for PD is questionable.…”
Section: α-Synucleinmentioning
confidence: 99%
“…Based on these significant findings, researchers have started to model PD based on the overexpression of the wild type or mutant forms of SNCA in animals. Many α-synuclein transgenic animal models have been proposed based on this model, with the subsequent experimental results revealing the pathology of PD [ 42 , 43 ]. The SNCA transgenic model can reproduce SNCA aggregation similar to that found in human PD.…”
Section: Pd Modelsmentioning
confidence: 99%